The Comparison of Electromyographic Activity of Selected Shoulder Girdle Muscles in Elite Table Tennis Players with and without Shoulder Impingement Syndrome during Forehand Topspin - Nazanin Meghdadi; Ali Yalfani; Hooman Minoonejad (Vesnu Publications, 2018)
Introduction: Shoulder injuries are very common in sports such as table tennis in which the athletes' upper limb operates higher than shoulder level. On the other hand, weak or inappropriate shoulder muscle activity can be related to incidence of an injury. The purpose of this study was to compare the activation of selected scapulohumeral muscles in table tennis athletes between healthy and shoulder impingement syndrome group during a strike of forehand topspin. Materials and Methods: Thirty national-level male table tennis players aged 20 to 28 years were selected purposefully and divided into shoulder impingement syndrome (n = 15), and healthy (n = 15) groups. The surface electromyographic activity of selected muscles from scapulothoracic and glenohumeral joints was recorded during the strike of forehand topspin. Results: The level of the activity of the serratus anterior muscle (P = 0.007) and supraspinatus muscle (P = 0.001) in the shoulder impingement syndrome group was significantly lower and the level of upper trapezius muscle activation in the shoulder impingement syndrome subjects was significantly higher (P = 0.009) in shoulder impingement syndrome group compared to the healthy group. However, no significant differences were observed in the activation level of lower trapezius (P = 0.301), anterior deltoid (P = 0.314), and biceps brachii (P = 0.291) muscles. Conclusion: The results of this study showed that patients with impingement syndrome demonstrated unnatural and changed levels of muscle activity in scapulohumeral articulation during the forehand topspin strike. The findings confirm the theories that shoulder impingement may be related to changes in the activity level of scapulothoracic and glenohumeral muscles.